Debating Resource-Driven Development: A Comparative Analysis of Media Coverage on the Pacific Northwest LNG Project in British Columbia - Chen, Sibo (Frontiers in Communication, 2020)
In Canada, the provincial government of British Columbia has been keen on building an export-oriented liquefied natural gas (LNG) industry since 2011. This paper examines media coverage of the Pacific NorthWest LNG project (PNW), which was considered as the flagship proposal leading the BC LNG development, until its abrupt cancellation in July 2017. The paper explores the differences between public, commercial, and independent media in energy reporting by tracing how six Canadian media outlets covered the rise and fall of PNW over a 36 month period. The comparative analysis reveals that when addressing the project's cancellation, fossil fuel advocates repeatedly deployed the “jobs killed by environmentalists” argument via opinion pieces appearing in commercial newspapers. This diagnosis, however, downplayed the far-reaching impacts of falling Asian LNG market conditions prior to the cancellation. By comparison, independent media played an important role in assisting LNG opponents to communicate PNW's fragile economic basis to a wide audience. Overall, these findings shed light upon the significance of independent media in supporting diverse news accounts of energy controversies.